2017
DOI: 10.1194/jlr.r075556
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of nuclear receptor agonists in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is characterized by an extensive accumulation of amyloid-β (Aβ) peptide, which triggers a set of deleterious processes, including synaptic dysfunction, inflammation, and neuronal injury, leading to neuronal loss and cognitive impairment. A large body of evidence supports that nuclear receptor (NR) activation could be a promising therapeutic approach for AD. NRs are ligand-activated transcription factors that regulate gene expression and have cell type-specific effects. In this review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 140 publications
(106 reference statements)
1
55
0
1
Order By: Relevance
“…PPARs and RXR receptors activation upregulates the expression of several synaptic related genes coding proteins engaged in excitatory neurotransmission [12,36]. Probably through these mechanism agonists of PPAR-α may have a promising effect in a mouse model of aging-dependent cognitive impairments [37,38]. Moreover, it was previously reported that RXR activation increases dendritic complexity and branching of neurons and differentiation [39,40] but it seems now that PPAR-α plays a key role in these processes.…”
Section: Ppar-α and Its Role In Neurotransmission In The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARs and RXR receptors activation upregulates the expression of several synaptic related genes coding proteins engaged in excitatory neurotransmission [12,36]. Probably through these mechanism agonists of PPAR-α may have a promising effect in a mouse model of aging-dependent cognitive impairments [37,38]. Moreover, it was previously reported that RXR activation increases dendritic complexity and branching of neurons and differentiation [39,40] but it seems now that PPAR-α plays a key role in these processes.…”
Section: Ppar-α and Its Role In Neurotransmission In The Brainmentioning
confidence: 99%
“…Some other last data indicate promising, positive effect of PPARs agonists [127][128][129][130][131][132][133][134][135]. Overall it seems that personalized gene-related therapy or personalized combination Reduces Aβ production [48] Decreases Aβ plaque accumulation Improves learning memory [55] Decreases Aβ accumulation and reverses memory deficits and anxiety symptoms [132] WY-14643 Decreases tau protein and inflammation markers Increases ability in Moris water test [37] GW7647 Regulates APP amyloidogenic processing Decreases the expression of sAPPβ and ability of BACE1 Reduces Aβ release and Aβ production [50] Fenofibrate Regulates oxidative stress accumulation [133] Fenofibrate Parkinson's disease Protects against the damaging effect of MPTP in a rat model Decreases inflammation [94,134] Cerebral injury Reduces suspectibility to stroke in apolipoprotein E-deficient animals Decreases cerebral infarct volume [135] of specific pharmacological compounds should be more efficient. The further studies on pharmacologically active compounds that target PGC-1α and PPARs are necessary.…”
Section: Ppar-α Natural and Synthetic Agonists: From Experiments To Cmentioning
confidence: 99%
“…and aging (10,11). Importantly, they play a regulatory role in diseases of aging including Alzheimer's disease (12,13), cardiovascular disease (14), and cancer (15). Given the commonality between pathogenic pathways regulated by nuclear receptors in age-related diseases and AMD, in an attempt to identify candidate receptors that may be important in disease initiation and progression, we previously developed a nuclear receptor atlas of human RPE cells, cells vulnerable in AMD (16).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by amyloid‐β (Aβ) deposition, excessive phosphorylation of tau protein, and neurofibrillary tangles (Hardy & Selkoe, 2002; Prince et al, 2013). It has a long preclinical phase and causes impairment of cognitive, disability, and dependency of daily life (Moutinho & Landreth, 2017). AD is the most common type of dementia (Alzheimer's Association, 2016; Goodman et al, 2017) and accounts for about 60%–70% in dementia cases (World Health Organization, 2019).…”
Section: Introductionmentioning
confidence: 99%